The Other Poet. The Ancient Reception of Hesiod. - Koning, Hugo H. (Mnemosyne, 2011)
The article offers information on the thesis "The Other Poet: The Ancient Reception of Hesiod," by Hugo H. Koning. It explores the nature, formation, and the use of Hesiod's image in Greek world from 700 BC to 300 AD. It states that the image is an approached within the framework to examine the poet image and its mnemonic process. It also mentions the image of Hesiod's fellowbard Homer which is essential to three different Hesiod reception.